Hubungan Jumlah Kunjungan Wisatawan Banyuwangi terhadap Pajak Hotel. Pajak Restoran dan Pajak Hiburan Kabupaten Banyuwangi - Masetya Mukti; Devita Silviana (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract The development of tourism sector is able to encourage support industries of tourism emerging, such as hotel industry, restaurant industry and entertainment industry. The existence of tourism supporting industries can increase the local revenue through taxes suc as hotel taxes, restaurant taxes and entertainment taxes. This study is aimed to determine about relationship of the tourist arrivels to the hotel tax, restaurant tax and entertainment tax. This research used periode data (times series) while the source data using secondary data, then analyzed by using the Pearson Product Moment Correlation method. The result showed that the number of travelers has significant correlation to the hotel tax of 84.5% restaurant tax 84%, entertainment tax of 84%. Keywords: Number of tourist arrival, hotel tax, restaurant tax, entertainment tax